2021
DOI: 10.3855/jidc.14305
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic recurrence of SARS-CoV-2 infection in healthcare workers recovered from COVID-19

Abstract: There is rising concern that patients who recover from COVID-19 may be at risk of recurrence. Increased rates of infection and recurrence in healthcare workers could cause the healthcare system collapse and a further worsening of the COVID-19 pandemic. Herein, we reported the clinically symptomatic recurrent COVID-19 cases in the two healthcare workers who treated and recovered from symptomatic and laboratory confirmed COVID-19. We discuss important questions in the COVID-19 pandemic waiting to be answered, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Likewise, 10 studies were identified via citation searching. These 10 were sought for retrieval and then assessed for eligibility [ 12 , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] ,…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, 10 studies were identified via citation searching. These 10 were sought for retrieval and then assessed for eligibility [ 12 , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] ,…”
Section: Resultsmentioning
confidence: 99%
“…Some studies reported that health-care workers who have intense and close contact with infected individuals can suffer from COVID-19 disease more than once. 1 Safe and effective COVID-19 treatments have yet to be developed, but vaccination is an effective strategy in stopping the spread of SARS-CoV-2. Several vaccines have become available for use in different parts of the world: Over 40 candidate vaccines are in human trials, and over 150 are in preclinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Seventy-two studies were determined to be of good quality while nine studies were of fair quality (S3 Table). Studies were primarily downgraded for unclear study objectives[63], incomplete case definition[16, 28, 48, 66, 67, 70, 77, 83], non-consecutive subject recruitment[19, 27, 30, 34, 38, 39, 4446, 49, 71, 79, 80, 86, 90], incomparable subjects[79], inadequate length of follow-up[43, 63], inadequate description of statistical methods[39, 46, 80] and inadequate description of results[39, 78]. The most common cause for downgrading studies was non-consecutive recruitment which raised concerns that the included sample could be biased towards a more severe presentation or included more individuals undergoing routine screening.…”
Section: Resultsmentioning
confidence: 99%